here, k = -1
recall that where is a constant.I'm also not sure what to do with 2e^x
(basically this means, when deriving something with a constant coefficient, you can pretty much ignore the constant, find the derivative of the function, and then affix (multiply by) the constant again.
what?! you wrote the same thing twice, of course they are the sameand is 1/e^x not 1/e^x?
1/(e^x) = e^(-x) if that makes it any easier for you
another common way to type e to some power is to type exp(some power)
so 1/(e^x) = e^(-x) = exp(-x)